2003
DOI: 10.1207/s15327663jcp1304_09
|View full text |Cite
|
Sign up to set email alerts
|

How Do Consumers Transfer Existing Knowledge? A Comparison of Analogy and Categorization Effects

Abstract: The trend in recent consumer research has been to emphasize the similarities between analogy and categorization. In this investigation, we merge the literature on analogy, categorization, and structure mapping theory to reach a better understanding of their differences. In 3 experiments, we compare consumers’ responses to analogy and categorization cues and find that analogy places much greater constraints on knowledge transfer than categorization by focusing consumers on relational similarities. Illustrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 22 publications
0
50
0
3
Order By: Relevance
“…In the marketing literature, analogies have been shown to be valuable in understanding new products (cf. Gregan-Paxton & John, 1997;Gregan-Paxton, Hibbard, Brunel, & Azar, 2002;Gregan-Paxton & Moreau, 2003) and in generating new product solutions (Dahl & Moreau, 2002). However, there has been a limited reference to the psycholinguistic framework of conceptual combinations, and none in the context of new product perception.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In the marketing literature, analogies have been shown to be valuable in understanding new products (cf. Gregan-Paxton & John, 1997;Gregan-Paxton, Hibbard, Brunel, & Azar, 2002;Gregan-Paxton & Moreau, 2003) and in generating new product solutions (Dahl & Moreau, 2002). However, there has been a limited reference to the psycholinguistic framework of conceptual combinations, and none in the context of new product perception.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…This research also adds to the developing body of knowledge in the marketing literature on the use of creative cognition (e.g., analogies) in new product perception. For instance, it has been shown that in the case of discontinuous new products (e.g., CD writers, digital cameras), the use of analogical transfers can aid the consumer learning of these products (Gregan-Paxton & John, 1997;Gregan-Paxton & Moreau, 2003;Moreau et al, 2001). Also, in a recent study in the context of new product ideation, Dahl and Moreau (2002) showed the value of using analogies in generating innovative new products.…”
Section: Theoretical Contributions and Managerial Implicationsmentioning
confidence: 99%
“…Knowledge transfer in the context of consumer research refers to the process by which consumers transfer existing, stored knowledge about a familiar product or situation to generate inferences and subsequently to learn about a new or unfamiliar product or situation (Gregan-Paxton & Moreau, 2003;.…”
Section: Analogical Knowledge Transfermentioning
confidence: 99%
“…Following previous research on knowledge transfer in consumer research (Gregan-Paxton & Moreau, 2003), the nature and extent of participants' internal knowledge transfer and inference generation was captured by having participants complete two cognitive response tasks. The first task asked participants, ''What does the ad headline tell you about the product?…”
Section: Relational Knowledge Transfermentioning
confidence: 99%
“…La recherche actuelle montre que l'utilisation de processus créatifs (ex : les analogies) permet d'améliorer la qualité (nouveauté perçue) des CNP générés par les créateurs (Dahl et Moreau, 2002). D'autres indices montrent que les analogies requiè-rent plus d'effort cognitif et demandent plus de connaissance de base pour être efficaces (GreganPaxton et Moreau, 2003 ;Roehm et Sternthal, 2001). Les combinaisons conceptuelles, d'un autre côté, sont plus fréquentes du fait de leur usage intensif dans le langage quotidien.…”
Section: Contributions Théoriques Et Implications Managérialesunclassified